2006
DOI: 10.1086/502794
|View full text |Cite
|
Sign up to set email alerts
|

New Relationships between Galaxy Properties and Host Halo Mass, and the Role of Feedbacks in Galaxy Formation

Abstract: We present new relationships between halo masses (M h ) and several galaxy properties, including r * -band luminosities (L r ), stellar (M star ) and baryonic masses, stellar velocity dispersions (σ), and black hole masses (M BH ). Approximate analytic expressions are given. In the galaxy halo mass range 3 × 10 10 M ⊙ ≤ M h ≤ 3 × 10 13 M ⊙ the M h -L r , M star -M h , and M BH -M h are well represented by a double power law, with a break at M h,break ≈ 3 × 10 11 M ⊙ , corresponding to a mass in stars M star ∼ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
394
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 299 publications
(443 citation statements)
references
References 92 publications
(175 reference statements)
47
394
0
1
Order By: Relevance
“…We note here that several other galaxy/AGN evolutionary models based on BH fuelling in bulges with no bar instabilities (e.g., Granato et al 2004;Cirasuolo et al 2005;Shankar et al 2006) have also suggested additional possible sources of the observed large scatter observed in BH scaling relations. A break in BH scaling relations at low masses induced by inefficiency of quasar compared to supernova feedback, responsible for shaping the galaxy stellar mass function (e.g., Shankar et al 2006, and references therein), and different normalizations of the M bh -M bulge relation at different virialization epochs of the host haloes, inevitably increase the predicted distribution of BH masses at fixed bulge mass.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We note here that several other galaxy/AGN evolutionary models based on BH fuelling in bulges with no bar instabilities (e.g., Granato et al 2004;Cirasuolo et al 2005;Shankar et al 2006) have also suggested additional possible sources of the observed large scatter observed in BH scaling relations. A break in BH scaling relations at low masses induced by inefficiency of quasar compared to supernova feedback, responsible for shaping the galaxy stellar mass function (e.g., Shankar et al 2006, and references therein), and different normalizations of the M bh -M bulge relation at different virialization epochs of the host haloes, inevitably increase the predicted distribution of BH masses at fixed bulge mass.…”
Section: Discussionmentioning
confidence: 49%
“…A break in BH scaling relations at low masses induced by inefficiency of quasar compared to supernova feedback, responsible for shaping the galaxy stellar mass function (e.g., Shankar et al 2006, and references therein), and different normalizations of the M bh -M bulge relation at different virialization epochs of the host haloes, inevitably increase the predicted distribution of BH masses at fixed bulge mass.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the amount of gas available for star formation, outflows mitigate the overcooling problem wherein too large a fraction of baryons condenses into stars (White & Rees 1978;Balogh et al 2001;Davé et al 2001). Moreover, stellar-feedback-driven outflows are frequently invoked to explain the sub-L * portion of the stellar mass-halo mass relation (e.g., Shankar et al 2006), and the simulations most successful in reproducing the stellar mass-halo mass relation typically employ strong stellar feedback Aumer et al 2013;Hopkins et al 2014). The efficiency of outflows across a range of galaxy masses is therefore key to determining the stellar and baryonic mass for different mass halos.…”
Section: Impact Of Outflows On Galaxiesmentioning
confidence: 99%
“…However, the discovery of the gamma-ray emitting Fermi Bubbles (FBs) and the associated multiwavelength features in the center of Milky Way (Su et al 2010) suggest that galactic outflows may be quite common, occurring in Milky-Way and lower mass galaxies frequently over their life-times. Supernova feedback is invoked to globally suppress star formation in halos less massive than 10 12 M⊙ (Shankar et al 2006;Sharma & Nath 2013). However, it is well-known that isolated supernovae fizzle out in less than a Myr, requiring overlapping supernovae to form a superbubble (e.g., Sharma et al 2014).…”
Section: Introductionmentioning
confidence: 99%